Effect of twin circular tunnels on ground acceleration responses during earthquakes - Chong, Pei Shen (Nanyang Technological University, 2020)
The emphasized development and growing number of underground tunnels had raised concerns on their potential impact on the surface responses under dynamic loading. This study served as a foundation towards the understanding of how twin circular tunnels could affect the ground acceleration responses under seismic loading by performing finite element analysis using PLAXIS 2D. The ground responses were analysed through their respective horizontal peak ground accelerations (PGA) to evaluate various parameters with respect to their effects on the ground acceleration responses, namely the embedment depth, diameter, and the centre-to-centre distance of the twin circular tunnels. In this study, the twin circular tunnels were embedded in 80 m loose sand above 20 m of bedrock in a 720 m wide model. Dynamic horizontal displacement was modelled after the California Earthquake in 2014 due to its similarities in PGA with the calculated worst-potential earthquake tremor in Singapore. Negative interfaces were added to the boundaries between the twin circular tunnels and the surroundings to simulate soil-structure interactions in reality. This study concluded that the presence of twin circular tunnels would amplify the ground acceleration responses under seismic loading. Embedment depth and diameter of the twin circular tunnels were identified to be positively correlated to the ground acceleration responses, while twin circular tunnels with difference centre-to-centre distance displayed little deviation and hence their effects were inconclusive.